PENERAPAN ALGORITMA ROUND ROBIN PADA PENJADWALAN PREVENTIVE MAINTENANCE DI PT. PASIFIK SATELIT NUSANTARA - Ahmad Zakir; Sheila Azhari Dalimunthe; Dedy Irwan (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
Scheduling is needed when several activities must be processed at a certain time. Good scheduling maximizes the effectiveness of the use of every activity, so scheduling is an important part of planning and controlling activities. At PT. Pasifik Satelit Nusantara, there are maintenance activities on the devices used by the preventive maintenance process customers needed so that no additional costs occur, so it needs to be done scheduling that can minimize downtime. For this reason, the schedule must be in accordance with the actual conditions in the company so as to minimize downtime so that the process of customer activity is not hampered by damaged equipment. In this study utilizing a round robin algorithm that can schedule human resources that carry out preventife maintenance activities. The author uses website-based media so that it can easily be used by company superiors to schedule technicians or workers.